Prospects of Immunotherapy for Triple-Negative Breast Cancer - Qiu, Dan; Zhang, Guijuan; Yan, Xianxin; Xiao, Xinqin; Ma, Xinyi; Lin, Shujun; Wu, Jieyan; Li, Xinyuan; Wang, Wandi; Liu, Junchen; Ma, Yi; Ma, Min (Frontiers in Oncology, 2022)
In the classification and typing of breast cancer, triple-negative breast cancer (TNBC) is one type of refractory breast cancer, whilst chemotherapy stays the traditional treatment methods. However, the impact of chemotherapy is short-lived and may lead to recurrence due to incomplete killing of tumor cells. The occurrence, development and relapse of breast cancer are relevant to T cell dysfunction, multiplied expression of related immune checkpoint molecules (ICIs) such as programmed death receptor 1 (PD-1), programmed cell death 1 ligand 1 (PD-L1) and cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) produce immunosuppressive effect. Immunotherapy (including immune checkpoint inhibitors, adoptive cellular immunotherapy, CAR-T immunotherapy and some potential treatments) provides new hope in TNBC. This review focuses on the new immune strategies of TNBC patients.